TECHNOLOGIES FOR DEVELOPING DIGITAL COMPETENCES IN STUDENTS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the issue of developing digital competencies of higher education students. The article analyzes the structure of digital competencies based on the European DigComp 2.2 framework model. According to the results of the study, blended learning and project-based learning methods demonstrate the highest efficiency in the formation of digital competencies. The article provides practical recommendations.
Keywords: digital competence, digital literacy, DigComp 2.2 framework model, higher education, blended learning, educational technologies.